Correlation of retinal vascular characteristics with laboratory and ocular findings in Fabry disease: exploring ocular diagnostic biomarkers - Lindziute, Migle; Kaufeld, Jessica; Hufendiek, Karsten; Volkmann, Ingo; Brockmann, Dorothee; Hosari, Sami; Hohberger, Bettina; Christian, Mirko; Framme, Carsten; Jan, Tode; Hufendiek, Katerina (Orphanet Journal of Rare Diseases, 2023)
Background: The goal of this study was to evaluate macular microvascular changes in patients with Fabry disease (FD) using optical coherence tomography angiography (OCTA) and to explore their correlation with laboratory and ocular findings. Methods: A total of 76 eyes (38 patients) and 48 eyes of 24 healthy controls were enrolled in this prospective study. Vessel Area Density (VAD) and Foveal Avascular Zone (FAZ) area were calculated on 2.9 × 2.9 mm OCTA images scanned with the Heidelberg Spectralis II (Heidelberg, Germany). VAD was measured in three layers: Superficial Vascular Plexus (SVP), Intermediate Capillary Plexus (ICP), and Deep Capillary Plexus (DCP). All scans were analyzed with the EA-Tool (Version 1.0), which was coded in MATLAB (The MathWorks Inc, R2017b). FAZ area was manually measured in full-thickness, SVP, ICP and DCP scans. Results: Average VAD in SVP, ICP and DCP was higher in Fabry disease patients than in controls (49.4 ± 11.0 vs. 26.5 ± 6.2, 29.6 ± 7.4 vs. 20.2 ± 4.4, 32.3 ± 8.8 vs. 21.7 ± 5.1 respectively, p < 0.001). Patients with cornea verticillata (CV) had a higher VAD in ICP and DCP compared to patients without CV (p < 0.01). Patients with increased lysoGb3 concentration had a higher VAD in DCP when compared to patients with normal lysoGb3 concentration (p < 0.04). There was no difference in VAD in patients with and without vascular tortuosity. However, a significantly higher VAD was observed in patients with vascular tortuosity compared to controls (p < 0.03). Conclusions: Increased lysoGb3 and VAD in DCP could be reliable biomarkers of disease activity. Cornea verticillata could be adopted as a predictive biomarker for VAD changes and disease progression. The combination of cornea verticillata and increased VAD may serve as a diagnostic biomarker for Fabry disease, however due to the discrepancies in VAD values in various studies, further research has to be done to address this claim.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Biomarkers; Fabry disease; OCT angiography; Vascular remodelling; Vessel area density